Improving Students’ Vocabulary Mastery Through the Keyword Technique At The Tenth Grade of SMAN 2 Tulang Bawang Tengah - Eva Nurchurifiani; Rizki Novia Nissa; Febriyanti Febriyanti (CV. Tripe Konsultan, 2021)
The aim of this research was to improve students’ vocabulary mastery of the tenth grade through the use of Keyword technique. This research is categorized as classroom action research. The subject of this research was the tenth grade students of SMAN 2 Tulang Bawang Tengah in the academic year of 2021/2022. The data were analyzed by using descriptive statistics and quantitative data analyses. This research was conducted in two cycles where each cycle consisted of three meetings. Based on the analysis of the research findings, the students’ vocabulary mastery was improved by using Keyword technique based on the quantitative and qualitative data. From quantitative data, the result showed that the mean score of each cycle was increased from post-test of cycle 1 to cycle 2. The mean score of cycle 1 was 62.07, there were 13 students or 46.43% who passed Minimum Mastery Criterion, while in cycle 2 was 77.93, there were 21 students or 75% who passed Minimum Mastery Criterion. Moreover, this improvement can also be seen from qualitative data, such as the results of students’ observation sheet from cycle 1 to cycle 2. The mean score of cycle 1 was 6.41, while in cycle 2 was 7.31. The improvement of students’ learning activity from cycle 1 to cycle 2 was 0.90. It showed that the students seemed to be more motivated and confidence in learning vocabulary. Therefore, it can be concluded that the implementation of the Keyword technique can improve students’ learning activities and vocabulary mastery.